TOXICO-ALLERGIC DERMATITIS IN CHILDREN - I.Yu. Mel'nikova; V.M. Shaitor ("Paediatrician" Publishers LLC, 2008)
15% of children in the world have allergic diseases (who data). The rate of allergic diseases in citizens of megapolices in Russia is 30-60%. The number of visits to the doctors increased on 18% in last 3 years. Generalized allergic reactions have leading place: anaphylactic shock and toxico-allergic dermatitis (steven johnson and lyell's syndromes). These diseases are characterized as pathology with fulminant course and frequently negative outcome. Literature data about this problem was analyzed in this article. The results of own researches in the field of urgent medical care on pre admission stage in children with generalized allergic reactions were presented.Key words: children generalized allergic reactions, urgent care.